Pelatihan Pengembangan Strategi Bisnis Sekolah Sepak Bola: Football School Business Strategy Development Training - Habyba, Anik Nur; Akbari, Annisa Dewi; Dewayana, Triwulandari Satitidjati; Maulidya, Rahmi; Suhardini, Didien; Surjasa, Dadang; Sari, Indah Permata (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
"KR" is a service-based business, a soccer school (SSB). This business was established to help students who enjoy soccer develop and train physically. A sports teacher and his colleagues founded the SSB. The current limited number of students has resulted in a lack of profit from one of the rented field locations over the past 2 years of operation. The SSB business remains unstable but is expected to grow. The purpose of this community service activity is to equip SSB managers with the knowledge and skills to formulate effective business strategies by developing an innovative, sustainable SSB business model. The results show that partners have successfully improved their understanding of the BMC concept, customer segments, and cost strategies. This Community Service Program is expected to serve as teaching materials, obtain IPR, and be published in a Sinta 4-accredited journal.